2018
DOI: 10.2166/wst.2018.405
|View full text |Cite
|
Sign up to set email alerts
|

Flocculation performance of anionic starch in oil sand tailings

Abstract: A series of carboxymethyl starches (CMSs), with various degrees of substitution from 0.1 to 0.79, were synthesized and selected as a model to study the feasibility of using natural polymers as flocculants for oil sand tailings treatment. The flocculation performance of modified CMS in kaolin clay suspensions and oil sand tailings was evaluated in terms of settling rate, solids content, capillary suction time, and specific resistance to filtration of the sediment phase. It was found that the synthesized CMS eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Na-CMS is a polymer produced on an industrial scale and is used in oil and gas [6,7], textile [8,9,10], pharmaceutical [11,12] industries, is used as a stabilizer for aqueous solutions, suspensions and emulsions, occulants, adhesive etc. [13,14,15]. In addition, aqueous solutions of Na-CMS are more stable and less prone to biodegradation compared to starch [16].…”
Section: Introductionmentioning
confidence: 99%
“…Na-CMS is a polymer produced on an industrial scale and is used in oil and gas [6,7], textile [8,9,10], pharmaceutical [11,12] industries, is used as a stabilizer for aqueous solutions, suspensions and emulsions, occulants, adhesive etc. [13,14,15]. In addition, aqueous solutions of Na-CMS are more stable and less prone to biodegradation compared to starch [16].…”
Section: Introductionmentioning
confidence: 99%
“…de Oliveira et al reported that chitosan, a cationic natural polysaccharide, modified with 3-chloro-2-hydroxypropyltrimethylammonium chloride, may be successfully used to treat oil sands MFT . Zhao et al reported that carboxymethylated starch (anionic starch) is also capable of dewatering oil sands tailings …”
Section: Introductionmentioning
confidence: 99%
“…16 Zhao et al reported that carboxymethylated starch (anionic starch) is also capable of dewatering oil sands tailings. 17 Very recently, we described the preparation of thermoresponsive starch nanoparticles (SNPs) by treating SNPs with butene oxide. 18 The resulting hydroxybutylated SNPs exhibited thermoresponsivity when the molar substitution (MS) was greater than 1.…”
Section: Introductionmentioning
confidence: 99%